2009
DOI: 10.1128/jvi.00546-09
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Integrated Copies and High-Level Production of the Human Retrovirus XMRV (Xenotropic Murine Leukemia Virus-Related Virus) from 22Rv1 Prostate Carcinoma Cells

Abstract: The human retrovirus XMRV (xenotropic murine leukemia virus-related virus) is associated with prostate cancer, most frequently in humans with a defect in the antiviral defense protein RNase L, suggesting a role for XMRV in prostate carcinogenesis. However, XMRV has not been found in prostate carcinoma cells. Here we show that 22Rv1 prostate carcinoma cells produce high-titer virus that is nearly identical in properties and sequence to XMRV isolated by others and consist primarily of a single clone of cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
163
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(168 citation statements)
references
References 12 publications
5
163
0
Order By: Relevance
“…Recent studies have provided evidence for integration of XMRV into the genomes of prostate tissues of cancer patients (7,17), as well as into the 22Rv1 prostate carcinoma cell line (18). However, evidence for common XMRV integration sites within or near protooncogenes or tumor suppressor genes in tumor tissues is still lacking (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided evidence for integration of XMRV into the genomes of prostate tissues of cancer patients (7,17), as well as into the 22Rv1 prostate carcinoma cell line (18). However, evidence for common XMRV integration sites within or near protooncogenes or tumor suppressor genes in tumor tissues is still lacking (17).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of this protein in Chinese hamster ovary (CHO) cells that are not known to express Xpr1 endogenously confers an enhanced susceptibility of these cells to xenotropic MuLV infection (2). Infection of hamster and mouse cells with XMRV-like virus that is derived from a prostate cancer cell line (22Rv1) also requires Xpr1 as a receptor (18). Earlier studies have demonstrated the importance of certain residues located within the putative third and fourth extracellular loops (ECL3 and ECL4) of Mus dunni's Xpr1 in conferring infection by xenotropic MuLVs (25).…”
mentioning
confidence: 99%
“…XMRV detection in a small percentage of samples from healthy controls suggested widespread infection (7,18,29). Controversy has since surrounded XMRV detection, partly because many laboratories have been unable to detect XMRV in patient samples (2, 5, 6, 8-11, 14, 16, 19-21, 28, 30, 35, 37, 40) and partly because an almost identical virus has been found infecting a common prostate cancer cell line called 22Rv1 (12,15,23). These data strongly suggest that XMRV in patient material is the result of DNA contamination from laboratory cell lines or mouse DNA.…”
mentioning
confidence: 99%
“…Consequently, we could not detect XMRV DNA in blood cells of CFS patients although plasma from two of 100 patients tested positive for the XMRV Gag antibody [4]. To quantitate infectious XMRV, Knouf et al and Metzger et al established a sarcoma-positive leukemia-negative (S+L-) assay that employed feline PG-4 cells, and also developed an alkaline phosphatase marker rescue assay using human HT-1080 cells [7,10]. In this study, we also tried to establish reliable methods to detect infectious XMRV.…”
mentioning
confidence: 99%
“…XMRV was prepared from the culture supernatant of HEK293T cells persistently infected with XMRV derived from 22Rv1 cells (ATCC: CRL-2505) [7]. Feline leukemia virus subgroup A (FeLV-A) was prepared from culture supernatant of HEK293 cells persistently infected with FeLV-A derived from an infectious molecular clone, pFGA-5 [11].…”
mentioning
confidence: 99%